Understanding entrainment processes in the atmosphere: the role of numerical simulation - van,Reeuwijk M; Jonker,HJJ (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
Turbulent entrainment is a process of primary importance in the atmospheric boundary layer; however despite several decades of intense study much remains to be understood. Direct Numerical Simulation (DNS) and Large-Eddy Simulation (LES) have a tremendous potential to improve the understanding of turbulent entrainment, particularly if combined with theory. We discuss a recently developed framework for turbulent jets and plumes to decompose turbulent entrainment in various physical processes, and modify it for use in a stably stratified shear driven (nocturnal) boundary layer. The decomposition shows that inner layer processes become negligible as time progresses and that the entrainment coefficient is determined by turbulence production in the outer layer only.